Methods for conducting an audit of the effectiveness of internal control - Marmilova, Ekaterina; Kashirskaya, Liudmila; Kuběnka, Michal; Turgaeva, Aksana; Zurnadzhyants, Yulia; Prodanova, Natalia (My University, 2020)
The socio-economic orientation of the insurance companies’ activity has identified this industry as one of the most strictly regulated by the state, which led to the obligatory implementation of internal control. The article discusses the methods of assessing the ICS and based on the studied researches; own methodology for conducting an audit of the effectiveness of internal control in an insurance company is proposed. This theme is especially relevant for insurance companies, where mechanisms of assessing the effectiveness of the internal control system are still being developed. The author proposes a new approach to assessing the effectiveness of the internal control system in an insurance organization based on quantitative and qualitative criteria of the use of an integrated indicator for assessing the effectiveness of ICS. An audit plan for the effectiveness of ICS in an insurance organization has been drawn up. The conditions for recognizing an effective system of internal control in an insurance organization are identified. The author proposed such components of the analytical procedure for assessing the effectiveness of internal control as testing and calculating an indicator characterizing the level of coverage of the internal control system.
Způsoby provedení auditu účinnosti vnitřní kontroly
Keywords: audit; internal control; insurance company; efficiency; assessment; integrated indicator; assessment methods; audit; vnitřní kontrola; pojišťovna; efektivita; hodnocení; integrovaný indikátor; metody hodnocení